Utilizing the Fuzzy Analytical Hierarchy Process (FAHP) approach to identify the best online food delivery services / Wan Nurul Husna Wan Nordin ...[et al.] - Wan Nordin, Wan Nurul Husna; Othman, Suziana Aida; Ramli, Masnira; Abdul Rashid, Syahirah Aqilah; Sukri, Nurul Najiha Najwa (2023)
The rapid growth of online food delivery (OFD) services has led to an overwhelming number of options available to consumers. Choosing the best service provider among the multitude of available options has become a complex decision-making process. This study proposes Fuzzy Analytical Hierarchy Process (FAHP) approach to evaluate and rank three popular OFDs: Foodpanda, GrabFood, and OdaMakan, among students at Universiti Teknologi MARA (UiTM) Kelantan Branch, Kota Bharu Campus. Three experts were invited to assess and rate the performance values of criteria and alternatives using a linguistic scale. The evaluation is based on four criteria: service, cost, time, and quality. The fuzzy set theory is utilized to transform the linguistic evaluation statements of experts into criteria weights that are produced by the FAHP. The results demonstrate the effectiveness of the FAHP in selecting the best OFD and that GrabFood is at the first ranking followed by Foodpanda and OdaMakan. Cost is identified as the most important criterion followed by time, service, and quality. The findings of this study can assist OFD providers in understanding the factors that contribute to customer satisfaction and help them to improve their services accordingly.